Algebra Advanced Techniques
Algebra Advanced Techniques
Algebra Advanced Techniques
Algebra techniques
Syllabus Content
A Basic Mathematics 10%
Page 1
2.1
What is algebra?
Subtraction
Multiplication
Division
Page 2
Simplifying expressions
Simplifying an algebraic expression means making it neater and usually shorter by
combining terms where possible. This involves collecting like terms into groups (e.g.
all the x or all the y) and then combining the like terms in each group (adding,
subtracting, multiplying or dividing them).
5x + 2x 8x =
(b) Simplify:
2t + 5i =
(c) Simplify:
s + 13s + s2 =
(d) Simplify:
(a + b)(c+ d) =
Page 3
(a + b)(c+ d) =
(a + b)(c+ d) = ac + ad + bc + bd
(b) (x + 6)(x - 3) =
(c) (1 - d)(2 - d) =
Page 4
Transposing equations
In the equation a = b + c/d we say that a is the subject of the equation. The subject
appears by itself on one side, usually the left, of the equation, and nowhere else. If we
are asked to transpose the equation for b, then we must rearrange the equation so that
b becomes the subject. The rules for transposing are as follows, but the key rule is
whatever you do to one side do to the other side
For example:
(b) y = 10g 4y
(c) y = 2/g
(d) y = 5/(9g + 4)
Page 6
Page 7
Page 8
Chapter 2
Page 9
Page 10
(b) y = 10g 4y
y + 4y = 10g 4y + 4y (add 4y to both sides, to leave 10g on its own)
5y = 10g
5y/10 = 10g/10 (divide both sides by 10, to leave g on its own)
y/2 = g
g = y/2
(c) y = 2/g
1/y = g/2 (reciprocate both sides)
(1/y) x 2 = (g/2) x 2 (multiply both sides by 2)
2/y = g
g = 2/y
(d) y = 5/(9g + 4)
1/y = (9g + 4)/5 (reciprocate both sides)
( 1/y ) x 5 = ( (9g + 4)/5 ) x 5 (multiply both sides by 5)
5/y = 9g + 4
5/y 4 = 9g + 4 4 (subtract both sides by 4)
5/y 4 = 9g
(5/y 4)/9 =9g/9 (divide both sides by 9)
(5/y 4)/9 = g
g = (5/y 4)/9
(e) Rearrange y = ax + b for x
y b = ax + b b (subtract both sides by b)
(y b)/a = x (divide both sides with a)
x = (y b)/a
Solve the following equations for y:
(f) 10(y + 4) = 24
y + 4 = 24/10 (divide both sides by 10)
y = 2.4 4 (subtract both sides by 4)
y = -1.6
(g) 4(y - 3) = 6(y - 9)
4y 12 = 6y - 48 (multiply out brackets on both sides)
4y 6y 12 = 6y 6y - 48 (subtract 6y from both sides)
-2y 12 = -48
-2y 12 +12 = -48 +12 (add both sides by 12)
-2y = -36
-2y/-2 = -36/-2 (divide both sides by 2)
y = 18
Page 11
Page 12
Page 13